STILL LIFE AS A GENRE OF MODERN LYRICS - Suchý, Viktor (Bohemica Olomucensia, 2021)
The paper deals with the possibility of transferring the term still life from visual arts to lyrical poetry. The focus is on Richard Weiner's ecphrastic poem Jean Baptiste Chardin, its analysis and interpretation.
Keywords: still life; poetry; modern lyrics; ecphrasis; spatiality; Richard Weiner; Chardin